The Effect Of Digital Marketing And Product Quality On Loyalty Through Customer Satisfaction In Chicken Noodle Business - Puput Nur Hidayah; Ismail Razak; Partogi S Samosir (Indonesian Journal Economic Review (IJER), 2026)
To determine the effect of digital marketing and product quality on loyalty through customer satisfaction of chicken noodle business. Based on the research objectives, this research is explanatory through hypothesis testing to examine the causal relationship between digital marketing variables, product quality, with customer satisfaction and loyalty. The data used in this study are primary data by conducting a survey by distributing questionnaires to mie ayam kota customers. The data analysis method used is descriptive analysis and path analysis. The results are in the form of the effect of digital marketing and product quality on loyalty through customer satisfaction of chicken noodle business.